2016
DOI: 10.1214/16-ejp4514
|View full text |Cite
|
Sign up to set email alerts
|

Continuum space limit of the genealogies of interacting Fleming-Viot processes on $\mathbb{Z}$

Abstract: We study the evolution of genealogies of a population of individuals, whose type frequencies result in an interacting Fleming-Viot process on Z. We construct and analyze the genealogical structure of the population in this genealogy-valued Fleming-Viot process as a marked metric measure space, with each individual carrying its spatial location as a mark. We then show that its time evolution converges to that of the genealogy of a continuum-sites stepping stone model on R, if space and time are scaled diffusive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
82
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(82 citation statements)
references
References 43 publications
0
82
0
Order By: Relevance
“…This means that in the recurrent case we have mono-ancestor and mono-type populations developing in any finite spatial window whereas in the transient case, locally we have coexistence of descendants of different ancestors and, if θ is not the point measure we also have coexistence of different types. This is proved in [GKW18] for the more general case of Λ-Fleming-Viot models, see [GSW16] for information on spatial tree-valued Fleming-Viot.…”
Section: (43)mentioning
confidence: 91%
See 1 more Smart Citation
“…This means that in the recurrent case we have mono-ancestor and mono-type populations developing in any finite spatial window whereas in the transient case, locally we have coexistence of descendants of different ancestors and, if θ is not the point measure we also have coexistence of different types. This is proved in [GKW18] for the more general case of Λ-Fleming-Viot models, see [GSW16] for information on spatial tree-valued Fleming-Viot.…”
Section: (43)mentioning
confidence: 91%
“…Mutation and selection have been included in [DGP12] leading to Í Á 1 -valued processes. Spatial models giving Í -valued Fleming-Viot processes were considered in [GSW16]. Both the latter are successively explained next in two paragraphs.…”
Section: Concepts and Examplesmentioning
confidence: 99%
“…whereẆ is space-time white noise and σ 2 = m. A related convergence result was proved for the long range voter model in [MT95], and for the spatial Λ-Fleming-Viot process in [EVY18]. A corresponding convergence result regarding the underlying genealogies was also proved in [GSW16].…”
Section: Introductionmentioning
confidence: 95%
“…This is done by applying the ergodic theorem to an auxiliary process which is defined in Subsection 3.2. Durrett and Restrepo [DR08] already showed that, in the stepping stone model with uniform population sizes and in the long range voter model, the time spent together by two lineages before they coalesce is asymptotically exponential (see also [Mar71] and [GSW16]). Theorem 2.8 extends this result to the stepping stone model in a random environment.…”
Section: Delayed Coalescence For Random Walks In a Random Environmentmentioning
confidence: 99%
“…Topology of the state space for spatial models In order to incorporate genealogies in spatial models it is necessary to generalize the concept of ultrametric measure spaces to marked ultrametric measure spaces. How to do this has been developed in [DGP11] and for infinite total population size in [GSW16]. We recall the idea.…”
Section: Generalizations: Discrete and Marked Settingmentioning
confidence: 99%